Formula of Yellow Kepok Banana (Musa acuminata x Musa balbisiana) Corm Extracts As Antiinflamation - Desy Muliana Wenas; Lisana Sidqi Aliya; Wisma Merry Anjani (Pusat Penelitian dan Pengembangan Perkebunan, 2019)
Bananas have many types and benefits. One of them is the Yellow Kepok Banana. Banana stem, leaf midrib, and corm contain phytochemicals compound as medicinal properties. The study aimed to determine the effect of the yellow kepok banana corm extract formula as an anti-inflammatory. Banana corm was cut into 0.3 x 1 x 3 cm pieces, dried in the oven with temperature 60 °C for 6 hours, then made 40 mesh powder. The powder extracted using 70 % ethanol by maceration technique for 24 hours, repeated three times. Anti-inflammatory testing was carried out on male Sprague Dawley white rats. A total of 24 white rats were divided into six treatment groups, consists of different concentrations of the extract (10, 15, and 20 %), positive control (commercial ointment), negative control, and a normal control (giving a wound without being given any formula). The experiment was designed as a randomized complete, with four replications, data were analyzed using ANOVA and the Post Hoc Games Howell Test. The results showed that the yellow kepok banana extract formula had the potential for wound healing. The 20 % extract formula can accelerate wound healing in a day than the 10 and 15 % formulas. The speed is shown by wound healing without scars from the 20 % extract formula, which occurs earlier than other formulas. The anti-inflammatory activity of the 20 % formula was comparable to the positive control of commercial ointment. The anti-inflammatory activity of the yellow kepok banana ointment formula is related to the compound of saponins, flavonoids, and tannins. The results indicate that the yellow kepok banana corm extract has the potential to be developed as an anti-inflammatory drug.